Nickel-zirconium composite catalyst as well as preparation method and application thereof
By using nickel-zirconium composite materials in photocatalytic technology, the problem of low utilization of sunlight by the catalyst is solved, efficient photothermal catalysis under the full spectrum is achieved, and the efficiency of reducing CO2 to methane is significantly improved.
Patent Information
- Application Number
- CN202310903128.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-21
AI Technical Summary
In the existing photocatalytic technology, the catalyst has a low utilization rate of sunlight, resulting in insufficient catalytic reaction power and the inability to efficiently utilize the full spectrum, especially visible and infrared light.
A nickel-zirconium composite material was designed, prepared by chemical deposition and metal-organic framework method. Ni element is evenly dispersed on the ZrO2 carrier, forming strong interaction and rich oxygen defects, which can absorb and activate CO2.
The nickel-zirconium composite material can efficiently absorb light energy in the full spectrum, convert it into thermal energy, and drive the reduction of CO2 to form methane, significantly improving the catalytic activity and methane selectivity without the need for external heating devices.
Smart Images

Figure CN119327458A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalyst preparation technology and application, and relates to a nickel-zirconium composite material and a preparation method and application thereof. Background Art
[0002] Fossil energy is the main driving force for the current economic development of human society. The consumption of a large amount of fossil fuels has brought huge economic benefits to mankind and improved human living standards, but it also produces a large amount of CO2, leading to the greenhouse effect and energy crisis. The International Climate Change Panel predicts that by 2100, the CO2 content in the earth's atmosphere will be as high as 590ppm, and the global average temperature will rise by 1.9℃. The global climate change caused by this will lead to unimaginable catastrophic consequences. In view of the serious impact of the rising concentration of CO2 in the atmosphere on the global climate, it is urgent to develop new technologies to remove or convert CO2.
[0003] Electrocatalytic technology directly degrades substrates through electrode reactions under the action of an external electric field, or utilizes the catalytic activity of electrodes or catalytic materials to generate a large number of strongly oxidizing free radicals and substrates to react; the advantage is that the process is simple and can be carried out at room temperature and pressure without secondary pollution, but it requires continuous replenishment of external energy; thermal catalytic technology injects energy that crosses the thermodynamic barrier into the catalytic reaction system in the form of thermal energy to drive the catalytic reaction. This technology is usually carried out at high temperature and high pressure, so the large consumption of energy has also become the biggest obstacle to the development of this technology; the basic principle of photocatalytic technology is: when light irradiates a semiconductor catalyst, if the energy of the photon is higher than the bandgap width of the semiconductor, the valence band electrons of the semiconductor jump from the valence band to the conduction band, and photogenerated electrons and holes are generated in the conduction band and valence band respectively. Holes have strong oxidizing ability, while photogenerated electrons have strong reducing ability, so that the electron acceptors on the surface of the semiconductor are reduced. However, due to their own energy band limitations, the catalysts currently used, such as WO3 (Journal of Materials Chemistry A, 2018, 6 (15): 6265-72.), ZrO2 (Applied Catalysis B: Environmental, 2017, 210 (131-40.), and ZnO (Journal of Materials Chemistry A, 2019, 7 (27): 16294-303.), can only respond to ultraviolet or part of visible light, and this part of light only accounts for about 47% of the full spectrum, that is, nearly 50% of sunlight is wasted (Journal of Materials Chemistry A, 2019, 7 (19): 11985-95). Therefore, improving the utilization rate of sunlight has become a research hotspot in the field of photocatalysis.
[0004] Taking into account the energy consumption of thermal catalysis and the low utilization rate of sunlight in traditional photocatalytic systems and the insufficient kinetic energy of catalytic reactions, it is of great significance to design catalysts that can efficiently utilize the full spectrum to make up for the low utilization rate of sunlight in traditional photocatalysis and achieve efficient light-driven thermal catalysis. Summary of the invention
[0005] The present invention provides a nickel-zirconium composite material, which is represented by the chemical formula Ni / ZrO2, wherein the carrier is ZrO2, the Ni element is uniformly dispersed on the carrier in the form of small-sized metallic nanoparticles, there is a strong interaction between Ni and ZrO2, and there are abundant oxygen defects on the surface.
[0006] According to an embodiment of the present invention, the loading amount of Ni element on the carrier is 10-80wt%, preferably 20-80wt%, more preferably 30-70wt%, for example 40wt%, 50wt% or 60wt%.
[0007] According to an embodiment of the present invention, the carrier ZrO2 is prepared by a metal organic framework method.
[0008] According to an embodiment of the present invention, the specific surface area of the nickel-zirconium composite material is 80-140 m 2 / g, preferably 90-130m 2 / g, for example, 94m 2 / g, 122m 2 / g, 91m 2 / g.
[0009] According to an embodiment of the present invention, the pore volume of the nickel-zirconium composite material is 0.2-0.8 cm 3 / g, preferably 0.3-0.7cm 3 / g, for example 0.40cm 3 / g,0.40cm 3 / g,0.40cm 3 / g.
[0010] According to an embodiment of the present invention, the average pore size of the nickel-zirconium composite material is 2-8 nm, preferably 3-7 nm, for example, 4.2 nm, 3.5 nm, 6.8 nm.
[0011] According to an embodiment of the present invention, the average particle size of Ni in the nickel-zirconium composite material is 30-50 nm, for example, 34.3 nm, 33.6 nm, 34.8 nm.
[0012] According to an embodiment of the present invention, the raw materials for preparing the nickel-zirconium composite material can be selected from the following compositions: nickel salts, zirconium salts and benzoic acid compounds; wherein the nickel salt can be selected from at least one of nickel nitrate (Ni(NO3)2·6H2O), nickel chloride (NiCl2·6H2O) and nickel acetate (Ni(CH3COO)2), preferably nickel nitrate; the zirconium salt can be selected from at least one of zirconium nitrate, zirconium chloride or zirconium carbonate, illustratively, the zirconium salt is zirconium chloride; further, the benzoic acid compound can be selected from at least one of benzene dicarboxylic acid compounds, benzene tricarboxylic acid compounds, benzene tetracarboxylic acid compounds, or benzene polycarboxylic acid compounds, preferably benzene dicarboxylic acid compounds. Exemplarily, the selected benzene dicarboxylic acid compound can be selected from terephthalic acid compounds and isophthalic acid compounds, illustratively, terephthalic acid.
[0013] Preferably, the composition may further include an organic solvent, which is not specifically limited in the present invention and may be selected from organic solvents known in the art, such as at least one of methanol, N,N-dimethylformamide, acetic acid, ethanol, isopropanol, triethanolamine, etc. Preferably, the organic solvent is selected from acetic acid and / or N,N-dimethylformamide. Exemplarily, the organic solvent is a mixed solvent of acetic acid and N,N-dimethylformamide, and the volume ratio of the two is 1:(12-20), preferably 1:(13-15), for example, 1:14.
[0014] The present invention also provides a method for preparing the above-mentioned nickel composite material, which comprises: using the above-mentioned composition to prepare a precursor of a nickel salt and a zirconium-based metal organic framework, and after calcining and reducing the precursor, obtaining the nickel-zirconium composite material, wherein the carrier is prepared by a metal organic framework method.
[0015] According to an embodiment of the present invention, the preparation method specifically comprises the following steps:
[0016] (1) zirconium salt, benzoic acid compound, acetic acid and N,N-dimethylformamide are synthesized by solvothermal method to prepare zirconium-based metal organic framework;
[0017] (2) uniformly mixing the nickel salt and the zirconium-based metal organic framework obtained in step (1), filtering and drying to obtain a uniformly dispersed precursor;
[0018] (3) The precursor of step (2) is subjected to air calcination and reduction to obtain the nickel-zirconium composite material.
[0019] According to an embodiment of the present invention, in step (1), the zirconium salt is zirconium nitrate, zirconium chloride or zirconium carbonate; illustratively, the zirconium salt is zirconium chloride.
[0020] According to an embodiment of the present invention, in step (1), the selected benzoic acid compound can be selected from at least one of a benzene dicarboxylic acid compound, a benzene tricarboxylic acid compound, a benzene tetracarboxylic acid compound, or a benzene polycarboxylic acid compound, and can be, for example, a benzene dicarboxylic acid compound. For example, the selected benzene dicarboxylic acid compound can be a terephthalic acid compound or an isophthalic acid compound, and for example, is terephthalic acid.
[0021] According to an embodiment of the present invention, in step (1), the synthesis time is 15-30 hours, preferably 20-25 hours.
[0022] According to an embodiment of the present invention, in step (1), the synthesis temperature is 100-180°C, preferably 100-140°C.
[0023] According to an embodiment of the present invention, the nickel salt described in step (2) is selected from at least one of nickel nitrate (Ni(NO3)2·6H2O), nickel chloride (NiCl2·6H2O) and nickel acetate (Ni(CH3COO)2), preferably nickel nitrate.
[0024] According to an embodiment of the present invention, in step (2), the amounts of the nickel salt, zirconium salt, benzoic acid type compound and zirconium salt are calculated based on the stoichiometric ratio required in the nickel-zirconium composite material.
[0025] According to an embodiment of the present invention, in step (2), the filtering and drying can be performed by using technical means known in the art.
[0026] Preferably, the drying temperature is 60-100° C., preferably 60-80° C.; preferably, the drying time is 1-24 hours, preferably 4-12 hours.
[0027] According to an embodiment of the present invention, the uniform mixing in step (2) can be obtained by ultrasound and / or stirring. Preferably, the ultrasound time is 5-30 minutes, preferably 5-10 minutes. Preferably, the stirring time is 2-24 hours, preferably 4-6 hours.
[0028] According to an exemplary embodiment of the present invention, in step (2), the uniform mixing includes dispersing the zirconium-based metal organic framework in water to obtain a zirconium-based metal organic framework aqueous solution, and then adding a nickel salt to the zirconium-based metal organic framework aqueous solution, and mixing after ultrasonication and stirring to obtain the material precursor. In the present invention, ultrasonication, stirring and other means help to anchor Ni ions in the pores of the zirconium-based metal organic framework, which is beneficial to promote the uniform dispersion of nickel particles and control the size of nickel particles.
[0029] According to an embodiment of the present invention, in step (3), the air roasting refers to roasting by introducing air.
[0030] Preferably, the air roasting temperature is 250-600°C, preferably 400-500°C, for example 450°C.
[0031] Preferably, the air roasting time is 5-15 hours, preferably 8-12 hours, for example 10 hours.
[0032] Preferably, during air roasting, the air flow rate is 10-200 mL / min, preferably 50-100 mL / min, for example 50 mL / min.
[0033] Preferably, the heating rate of air roasting is 1-10°C / min, preferably 1-5°C / min, for example 2°C / min.
[0034] According to an embodiment of the present invention, in step (3), the reduction roasting refers to roasting by introducing a reducing gas, such as hydrogen.
[0035] Preferably, the reduction roasting temperature is 300-600°C, preferably 350-450°C, for example 400°C.
[0036] Preferably, the reduction roasting time is 2-10 hours, preferably 2-4 hours, for example 2 hours.
[0037] Preferably, the flow rate of the reducing gas is 10-100 mL / min, preferably 20-50 mL / min, such as 30 mL / min.
[0038] Preferably, the heating rate of the reduction roasting is 1-10°C / min, preferably 3-8°C / min, for example 5°C / min.
[0039] According to an exemplary embodiment of the present invention, the method for preparing the nickel-zirconium composite material comprises the following steps:
[0040] (1) uniformly mixing zirconium salt, benzoic acid type compound, acetic acid and N,N-dimethylformamide, and synthesizing a zirconium-based metal organic framework by a solvothermal method;
[0041] (2) dispersing the zirconium-based metal organic framework in water to obtain a zirconium-based metal organic framework aqueous solution;
[0042] (3) adding nickel salt to the zirconium-based metal organic framework aqueous solution, mixing evenly, filtering, and drying to obtain a precursor;
[0043] (4) The material precursor obtained in step (3) is calcined in an air atmosphere and a hydrogen atmosphere successively to obtain the nickel-zirconium composite material.
[0044] The present invention also provides the use of the nickel-zirconium composite material as a catalyst, preferably in the catalytic CO2 methanation reaction. Preferably, the catalysis is photothermal catalysis; more preferably, the photothermal catalysis is to use the nickel-zirconium composite material to absorb full-spectrum (at least one of visible light, infrared light and ultraviolet light) light energy as the driving energy source for the reaction. Exemplarily, a full-spectrum light source is selected as the driving light source to convert the absorbed light energy into heat energy, thereby catalyzing CO2 methanation. Furthermore, the incident light intensity used in the photothermal catalysis can be 2-3W / cm 2 , for example, the incident intensity can be 2900 mW / cm 2 .
[0045] The present invention also provides a method for photothermal catalytic CO2 methanation, which comprises: the nickel-zirconium composite material absorbs light energy of at least one of visible light, infrared light and ultraviolet light (preferably, a full-spectrum light source is selected as a driving light source), converts the absorbed light energy into heat energy, and then catalyzes CO2 methanation.
[0046] Beneficial effects of the present invention:
[0047] The nickel-zirconium composite material provided by the present invention is a nickel-loaded ZrO2 material, with strong interaction between Ni and Zr, and rich surface oxygen defects, which can absorb and activate CO2, and make full use of the heat energy converted from light energy, and efficiently drive CO2 to reduce and form methane. The nickel-zirconium composite material synthesized by the present invention has high light absorption and good photothermal conversion ability, and has high activity and high methane selectivity, and has good application prospects.
[0048] Specifically, it has the following advantages:
[0049] (1) The preparation method provided by the present invention has easy-to-obtain raw materials, simple process and easy industrialization in the synthesis of highly uniformly mixed nickel-zirconium composite materials;
[0050] (2) The preparation method provided by the present invention utilizes the porous characteristics of the zirconium-based metal organic framework during the preparation process to uniformly adsorb nickel ions in the pores of the organic framework, and the synthesized zirconium-based metal organic framework and nickel salt are uniformly combined, and a strong interaction is formed between Ni and Zr during the roasting process; the synthesized uniformly dispersed nickel-loaded ZrO2-based material, after hydrogen roasting and reduction, the zero-valent Ni still has the characteristics of highly dispersed and small size, and due to the hydrogen overflow effect, abundant surface oxygen defects are formed on the surface of the material, which greatly enhances the material's ability to adsorb and activate CO2, and can efficiently realize the conversion of CO2 to CH4.
[0051] (3) When the material of the present invention is used as a catalyst, photothermal conditions can be achieved without the need for an external heating device. The nickel-loaded ZrO2 material can achieve strong light absorption in the full spectrum, and the catalytic activity is significantly improved. The composite material of the present invention is used as a catalyst to convert the absorbed light energy into heat energy, and efficient CO2 photo-methanization can be achieved without the use of an external heating device.
[0052] (4) The composite material of the present invention can be used as a catalyst and still maintain high catalytic activity and stability after a long period of catalytic experiment. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 It is the X-ray diffraction pattern of the materials of Examples 1-3 and Comparative Examples 1 and 2.
[0054] Figure 2 Transmission electron microscopy images of the nickel-zirconium composite material of Example 1 (left) and the catalyst of Comparative Example 2 (right).
[0055] Figure 3 The element distribution surface scan of the nickel-zirconium composite material of Example 1 (left) and the element distribution surface scan of the catalyst of Comparative Example 1 (right).
[0056] Figure 4 This is a comparison chart of the UV-visible diffuse reflectance spectra of nickel-zirconium composite materials.
[0057] Figure 5 The hydrogen temperature-programmed reduction spectra of the nickel-zirconium composite material of Example 1 and the catalysts of Comparative Examples 1 and 2 are shown.
[0058] Figure 6 The electron paramagnetic resonance spectra of the nickel-zirconium composite material of Example 1 and Comparative Example 1 are shown.
[0059] Figure 7 This is a graph showing the rate of CH4 and CO being generated when the materials of Examples 1-3 and Comparative Examples 1-2 are used as catalysts.
[0060] Figure 8 Graph showing CH4 yield and catalyst surface temperature of the nickel-zirconium composite material of Example 1 under different light intensities.
[0061] Fig. 9 The CH4 generation rate and CH4 generation selectivity of the nickel-zirconium composite material of Example 1 in the durability experiment are shown.
[0062] Fig.10 This is a rate diagram of CH4 and CO generated by the nickel-zirconium composite material of Example 1 under different light zone control conditions. DETAILED DESCRIPTION
[0063] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0064] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0065] Example 1
[0066] The preparation process of the nickel-zirconium composite material of this embodiment includes the following steps:
[0067] Step 1: Take 233.04 mg of zirconium chloride and dissolve it in 25 mL of N, N-dimethylformamide to make a uniform zirconium chloride solution, take 166.13 mg of terephthalic acid and dissolve it in 25 mL of N, N-dimethylformamide to make a uniform solution, mix and stir the above two solutions for 10 minutes, then add 3.6 mL of acetic acid, stir vigorously for 30 minutes, transfer to an autoclave, and place it in an oven and heat it to 120°C for 24 hours. After the autoclave cools down, centrifuge to remove the sample, then disperse the sample in methanol, finally centrifuge and vacuum dry it at 80°C overnight to obtain a zirconium-based metal organic framework;
[0068] Step 2: Take 200 mg of the above zirconium-based metal organic framework, disperse it in 100 mL of water, and stir it ultrasonically for 10 minutes; take 394.71 mg of Ni(NO)3·6H2O and add it to the above solution, ultrasonicate it for 30 minutes, stir it for 6 hours, then filter it, place it in an oven at 80°C and dry it for 12 hours to obtain a uniformly dispersed nickel salt and zirconium-based metal organic framework precursor;
[0069] Step 3: Place the dried precursor in a quartz tube, raise the temperature to 450°C at a rate of 2°C / min in an air atmosphere of 50mL / min, and maintain for 10 hours to obtain 50NiO / ZrO2;
[0070] Step 4: Place the sample calcined in air atmosphere in a quartz tube, and raise the temperature to 400°C at a rate of 5°C / min in a hydrogen atmosphere of 30 mL / min, and maintain it for 2 hours.
[0071] Step 5: Take out the reduced sample and blow off the H2 adsorbed on the surface with N2 to obtain 50Ni / ZrO2 material.
[0072] After the material of this embodiment was subjected to ICP testing, it was found that the actual loading amount of Ni was 50.8wt% (ie, the mass ratio of Ni:(Ni+ZrO2) was 50.8wt%).
[0073] Example 2
[0074] The preparation process of the nickel-zirconium composite material of this embodiment includes the following steps:
[0075] Step 1: Take 233.04 mg of zirconium chloride and dissolve it in 25 mL of N, N-dimethylformamide to make a uniform zirconium chloride solution, take 166.13 mg of terephthalic acid and dissolve it in 25 mL of N, N-dimethylformamide to make a uniform solution, mix and stir the above two solutions for 10 minutes, then add 3.6 mL of acetic acid, stir vigorously for 30 minutes, transfer to an autoclave, and place it in an oven and heat it to 120°C for 24 hours. After the autoclave cools down, centrifuge to remove the sample, then disperse the sample in methanol and stir, finally centrifuge and vacuum dry it at 80°C overnight to obtain a zirconium-based metal organic framework;
[0076] Step 2: Take 200 mg of the above zirconium-based metal organic framework, disperse it in 100 mL of water, and stir it ultrasonically for 10 minutes; take 263.14 mg of Ni(NO)3·6H2O and add it to the above solution, ultrasonicate it for 30 minutes, stir it for 6 hours, then filter it and place it in an oven at 80°C to dry it for 12 hours to obtain a uniformly dispersed nickel salt and zirconium-based metal organic framework precursor;
[0077] Step 3: Place the dried precursor in a quartz tube, raise the temperature to 450°C at a rate of 2°C / min in an air atmosphere of 50 mL / min, and maintain for 10 hours to obtain 40NiO / ZrO2;
[0078] Step 4: Place the sample calcined in air atmosphere in a quartz tube, and raise the temperature to 400°C at a rate of 5°C / min in a hydrogen atmosphere of 30 mL / min, and maintain it for 2 hours.
[0079] Step 5: Take out the reduced sample and blow off the H2 adsorbed on the surface with N2 to obtain 40Ni / ZrO2 material.
[0080] After the material of this embodiment was subjected to ICP testing, it was found that the actual loading amount of Ni was 40.7wt% (ie, the mass ratio of Ni:(Ni+ZrO2) was 40.7wt%).
[0081] Example 3
[0082] The preparation process of the nickel-zirconium composite material of this embodiment includes the following steps:
[0083] Step 1: Take 233.04 mg of zirconium chloride and dissolve it in 25 mL of N, N-dimethylformamide to make a uniform zirconium chloride solution, take 166.13 mg of terephthalic acid and dissolve it in 25 mL of N, N-dimethylformamide to make a uniform solution, mix and stir the above two solutions for 10 minutes, then add 3.6 mL of acetic acid, stir vigorously for 30 minutes, transfer to an autoclave, and place it in an oven and heat it to 120°C for 24 hours. After the autoclave cools down, centrifuge to remove the sample, then disperse the sample in methanol and stir, finally centrifuge and vacuum dry it at 80°C overnight to obtain a zirconium-based metal organic framework;
[0084] Step 2: Take 200 mg of the above zirconium-based metal organic framework, disperse it in 100 mL of water, and stir it ultrasonically for 10 minutes. Take 593.20 mg of Ni(NO)3·6H2O and add it to the above solution, ultrasonicate it for 30 minutes, stir it for 6 hours, and then filter it and place it in an oven at 80°C to dry it for 12 hours to obtain a uniformly dispersed nickel salt and a precursor of the zirconium-based metal organic framework.
[0085] Step 3: Place the dried precursor in a quartz tube, raise the temperature to 450°C at a rate of 2°C / min in an air atmosphere of 50 mL / min, and maintain for 10 hours to obtain 60NiO / ZrO2;
[0086] Step 4: Place the sample calcined in air atmosphere in a quartz tube, and raise the temperature to 400°C at a rate of 5°C / min in a hydrogen atmosphere of 30 mL / min, and maintain it for 2 hours.
[0087] Step 5: Take out the reduced sample and blow off the H2 adsorbed on the surface with N2 to obtain 60Ni / ZrO2 material.
[0088] After the material of this embodiment was subjected to ICP testing, it was found that the actual loading amount of Ni was 61.6wt% (ie, the mass ratio of Ni:(Ni+ZrO2) was 61.6wt%).
[0089] Comparative Example 1
[0090] The synthesis of commercial ZrO2-loaded nickel-based materials includes the following steps:
[0091] Step 1: 79.67 g of commercial ZrO2 (purchased from Shanghai Macklin Biochemical Co. Ltd.) was dispersed in 100 mL of water and stirred by ultrasonic for 10 min; 394.71 mg of Ni(NO)3·6H2O was added to the above solution, ultrasonicated for 30 min, stirred for 6 hours, then filtered and dried in an oven at 80°C for 12 hours to obtain a precursor of nickel salt and commercial ZrO2;
[0092] Step 2: Place the dried precursor in a quartz tube, raise the temperature to 450°C at a rate of 2°C / min in an air atmosphere of 50 mL / min, and maintain for 10 hours to obtain 50NiO / C-ZrO2 (C-ZrO2 is the abbreviation of Commercial zirconiumdioxide);
[0093] Step 3: Place the sample calcined in air atmosphere in a quartz tube, and raise the temperature to 400°C at a rate of 5°C / min in a hydrogen atmosphere of 30 mL / min, and keep it for 2 hours;
[0094] Step 4: Take out the reduced sample and blow off the H2 adsorbed on the surface with N2 to obtain 50Ni / C-ZrO2 material.
[0095] After the material of this embodiment was subjected to ICP testing, it was found that the actual loading amount of Ni was 50.2wt% (ie, the mass ratio of Ni:(Ni+ZrO2) was 50.2wt%).
[0096] Comparative Example 2
[0097] The ZrO2 material is prepared using the metal organic framework as a template. The specific preparation process includes the following steps:
[0098] Step 1: Take 233.04 mg of zirconium chloride and dissolve it in 25 mL of N, N-dimethylformamide to make a uniform zirconium chloride solution, take 166.13 mg of terephthalic acid and dissolve it in 25 mL of N, N-dimethylformamide to make a uniform solution, mix and stir the above two solutions for 10 minutes, then add 3.6 mL of acetic acid, stir vigorously for 30 minutes, transfer to an autoclave, and place it in an oven and heat it to 120°C for 24 hours. After the autoclave cools down, centrifuge to remove the sample, then disperse the sample in methanol and stir, finally centrifuge and vacuum dry it at 80°C overnight to obtain a zirconium-based metal organic framework;
[0099] Step 2: Take 200 mg of the above zirconium-based metal organic framework, place it in a quartz tube, and raise the temperature to 450°C at a rate of 2°C / min in an air atmosphere of 50 mL / min, and keep it for 10 hours;
[0100] Step 3: Place the sample calcined in air atmosphere in a quartz tube, and raise the temperature to 400°C at a rate of 5°C / min in a hydrogen atmosphere of 30 mL / min, and maintain it for 2 hours.
[0101] Step 4: Take out the reduced sample and blow away the H2 adsorbed on the surface with N2 to obtain ZrO2 material.
[0102] Figure 1 The X-ray diffraction patterns of the materials of Examples 1-3 and Comparative Examples 1 and 2 show that Ni is uniformly dispersed on ZrO2.
[0103] Figure 2 TEM images of the material of Example 1 (left) and the material of Comparative Example 2 (right).
[0104] The physical adsorption of the materials prepared in Examples 1-3 and Comparative Examples 1-2 is shown in Table 1.
[0105] Table 1
[0106]
[0107] Figure 3 The element distribution surface scan of the nickel-zirconium composite material 50Ni / ZrO2 prepared in Example 1 (left) and the element distribution surface scan of the catalyst 50Ni / C-ZrO2 prepared in Comparative Example 1 (right). Figure 3 It can be seen that compared with the catalyst of Comparative Example 1, the nickel-zirconium composite material prepared in Example 1 has more uniform dispersion of Ni and Zr, indicating that the interaction between the two is enhanced, and the uniform dispersion of nickel also provides more active sites for the reaction, which is one of the reasons why the nickel-zirconium composite material of Example 1 has higher reaction activity.
[0108] Figure 4 The UV-visible diffuse reflectance spectra of the materials prepared in Examples 1-3 and Comparative Examples 1 and 2 are compared. Figure 4 It can be seen that the nickel-zirconium composite materials prepared in Examples 1-3 have higher light absorption intensities than the catalysts in Comparative Examples 1 and 2 in the full spectrum, indicating that the nickel-zirconium composite materials of the present invention can achieve effective absorption of light in the full spectrum. This is because in the nickel-zirconium composite materials prepared in the present invention, Ni is evenly dispersed, has more surface oxygen defects, and the porous MOF structure has more, which can enhance the light absorption effect.
[0109] Figure 5The hydrogen temperature-programmed reduction spectra of the catalysts prepared in Example 1, Comparative Examples 1 and 2 are shown in FIG. Figure 5 It can be seen that the reduction peak of Ni in the nickel-zirconium composite material 50Ni / ZrO2 prepared in Example 1 shows a higher temperature reduction peak than that in the catalyst 50Ni / C-ZrO2 in Comparative Example 1; the catalyst in Comparative Example 2 has almost no peak signal. This indicates that in the nickel-zirconium composite material of the present invention, Ni and the carrier are more closely combined, and it is easier to generate surface oxygen vacancies.
[0110] Figure 6 The electron paramagnetic resonance spectra of the materials prepared in Example 1 and Comparative Example 1 are as follows: Figure 6 It can be seen that the nickel-zirconium composite material 50Ni / ZrO2 prepared in Example 1 shows a higher oxygen vacancy signal than the catalyst 50Ni / C-ZrO2 of Comparative Example 1 at a low temperature of -174°C, indicating that there are abundant defect sites on the surface of 50Ni / ZrO2.
[0111] Example 4
[0112] Evaluation of the catalytic activity of nickel-zirconium composite materials as catalysts under dynamic conditions (evaluation of the catalyst by testing the rate of production of CO2 to CH4 and CO)
[0113] The reactor used was a cylindrical stainless steel reactor with a quartz window. Before the experiment, 10 mg of each of the materials prepared in the above Examples 1-3 and Comparative Examples 1-2 were weighed as samples and spread on the surface of the quartz wool in the center of the reactor.
[0114] A mixture of CO2, H2 and He (volume ratio 1:4:5, volume flow rate 25mL / min, gas source: Xiamen Linde Gas Co., Ltd.) was introduced into the reactor for 30 minutes, and then the light was turned on for reaction. The light source used during the reaction was a simulated full-spectrum xenon lamp (PLS-SXE300UV, full spectrum). The products CH4 and CO produced during the reaction were detected by gas chromatography, where the CH4 generation rate and CO generation rate were respectively expressed by the following formulas (1) and (2):
[0115] CH4 production rate (mmol / g·h) = [CH4] / (catalyst mass*reaction time) (1)
[0116] CO generation rate (mmol / g·h) = [CO] / (catalyst mass*reaction time) (2)
[0117] The [CH4] and [CO] used are all molar concentrations.
[0118] Figure 7The nickel-zirconium composite materials prepared in Examples 1-3 and Comparative Examples 1-2 were heated under the conditions of Example 4 (light intensity was 2900 mW / cm 2 ) CH4 and CO generation rate diagram (left). It shows that the materials prepared in Examples 1-3 have a strong CH4 generation rate and methane selectivity, which is much higher than that of Comparative Example 1. By properly adjusting the amount of nickel loaded in the nickel-zirconium composite material of the present invention, the reaction activity can be further controlled, among which the nickel-zirconium composite material prepared in Example 1 shows the highest CH4 generation rate.
[0119] Figure 8 The graph of CH4 production rate and surface temperature when the nickel-zirconium composite material of Example 1 is used as a catalyst under the test conditions of Example 4 and changes in light intensity indicates that temperature has a significant effect on the activity of the nickel-zirconium composite material.
[0120] Fig. 9 The material of Example 1 was used as a catalyst under the test conditions of Example 4 (light intensity of 2900 m W / cm 2 ) After 10 hours of durability test, the CH4 rate and selectivity diagram were generated, which shows that the nickel-zirconium composite material of the present invention has a good and stable methane yield and excellent selectivity when used as a catalyst, and can be put into practical application.
[0121] Fig.10 The nickel-zirconium composite material prepared in Example 1 is used as a catalyst to generate CH4 and CO in different light zones (under the test conditions of Example 4, filters are used to obtain different wavelengths of light required for the test). The results show that the nickel-zirconium composite material prepared in Example 1 has similar CH4 and CO yields at the same temperature (394°C, 374°C) in different light zones, which indicates that the methanation of CO2 catalyzed by the nickel-zirconium composite material prepared in the present invention is a photothermal catalytic reduction reaction.
[0122] The exemplary embodiments of the present invention are described above. However, the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A nickel-zirconium composite material, characterized in that: The composite material is represented by the chemical formula Ni / ZrO2, wherein the carrier is ZrO2, and the Ni element is uniformly dispersed on the carrier in the form of small-sized metal nickel nanoparticles. Preferably, the loading amount of the Ni element on the carrier is 10-80wt%, preferably 20-80wt%, more preferably 30-70wt%.
2. The nickel-zirconium composite material according to claim 1, characterized in that The carrier ZrO2 is prepared by a metal organic framework method. Preferably, the specific surface area of the nickel-zirconium composite material is 80-140 m 2 / g, preferably 90-130m 2 / g. Preferably, the pore volume of the nickel-zirconium composite material is 0.2-0.8 cm 3 / g, preferably 0.3-0.7cm 3 / g. Preferably, the average pore size of the nickel-zirconium composite material is 2-8 nm, preferably 3-7 nm. Preferably, the average particle size of Ni in the nickel-zirconium composite material is 30-50 nm.
3. The nickel-zirconium composite material according to claim 1 or 2, characterized in that: The raw materials for preparing the composite material can be selected from the following composition: nickel salt, zirconium salt and benzoic acid type compound; wherein the nickel salt can be selected from at least one of nickel nitrate (Ni(NO3)2·6H2O), nickel chloride (NiCl2·6H2O) and nickel acetate (Ni(CH3COO)2); the zirconium salt can be selected from at least one of zirconium nitrate, zirconium chloride or zirconium carbonate; Preferably, the benzoic acid compound is selected from at least one of a benzene dicarboxylic acid compound, a benzene tricarboxylic acid compound, a benzene tetracarboxylic acid compound or a benzene polycarboxylic acid compound. Preferably, the composition may further include an organic solvent. Preferably, the organic solvent is selected from at least one of methanol, N,N-dimethylformamide, acetic acid, ethanol, isopropanol, triethanolamine and the like.
4. The method for preparing the nickel-zirconium composite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: using the composition according to claim 3 to prepare a precursor of a nickel salt and a zirconium-based metal organic framework, and the precursor is calcined and reduced to obtain the nickel-zirconium composite material.
5. The preparation method according to claim 4, characterized in that: The carrier is prepared by a metal organic framework method. Preferably, the preparation method specifically comprises the following steps: (1) zirconium salt, benzoic acid compound, acetic acid and N,N-dimethylformamide are synthesized by solvothermal method to prepare zirconium-based metal organic framework; (2) uniformly mixing the nickel salt and the zirconium-based metal organic framework obtained in step (1), filtering and drying to obtain a precursor with uniform dispersion; (3) The precursor of step (2) is subjected to air roasting and reduction roasting to obtain the nickel-zirconium composite material. Preferably, in step (1), the zirconium salt may be selected from at least one of zirconium nitrate, zirconium chloride or zirconium carbonate. Preferably, in step (1), the selected benzoic acid compound can be selected from at least one of a benzene dicarboxylic acid compound, a benzene tricarboxylic acid compound, a benzene tetracarboxylic acid compound, or a benzene polycarboxylic acid compound. Preferably, in step (1), the synthesis time is 15-30 hours, preferably 20-25 hours. Preferably, in step (1), the synthesis temperature is 100-180°C, preferably 100-140°C.
6. The preparation method according to claim 4 or 5, characterized in that: The nickel salt described in step (2) is selected from at least one of nickel nitrate (Ni(NO3)2·6H2O), nickel chloride (NiCl2·6H2O), and nickel acetate (Ni(CH3COO)2). Preferably, the drying temperature is 60-100° C., preferably 60-80° C.; preferably, the drying time is 1-24 hours, preferably 4-12 hours.
7. The preparation method according to any one of claims 4 to 6, characterized in that: In step (3), the air roasting refers to roasting by introducing air. Preferably, the air roasting temperature is 250-600°C, preferably 400-500°C. Preferably, the air roasting time is 5-15 hours, preferably 8-12 hours. Preferably, during air roasting, the air flow rate is 10-200 mL / min, preferably 50-100 mL / min. Preferably, the heating rate of air roasting is 1-10°C / min, preferably 1-5°C / min. Preferably, in step (3), the reduction roasting refers to roasting by introducing a reducing gas. Preferably, the reduction roasting temperature is 300-600°C, preferably 350-450°C. Preferably, the reduction roasting time is 2-10 hours, preferably 2-4 hours. Preferably, the flow rate of the reducing gas is 10-100 mL / min, preferably 20-50 mL / min. Preferably, the heating rate of the reduction roasting is 1-10°C / min, preferably 3-8°C / min.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The preparation method of the nickel-zirconium composite material comprises the following steps: (1) uniformly mixing zirconium salt, benzoic acid type compound, acetic acid and N,N-dimethylformamide, and synthesizing a zirconium-based metal organic framework by a solvothermal method; (2) dispersing the zirconium-based metal organic framework and the nickel salt in water respectively to obtain a nickel salt aqueous solution and a zirconium-based metal organic framework aqueous solution; (3) uniformly mixing the nickel salt aqueous solution and the zirconium-based metal organic framework aqueous solution, filtering and drying to obtain a precursor; (4) The precursor obtained in step (3) is calcined in an air atmosphere and a hydrogen atmosphere successively to obtain the nickel-zirconium composite material.
9. Use of the nickel-zirconium composite material according to any one of claims 1 to 3 as a catalyst, preferably in catalyzing CO2 methanation reaction. Preferably, the catalysis is photothermal catalysis. More preferably, the photothermal catalysis is to use the nickel-zirconium composite material to absorb full-spectrum (at least one of visible light, infrared light and ultraviolet light) light energy as the driving energy for the reaction. Exemplarily, a full-spectrum light source is selected as the driving light source to convert the absorbed light energy into heat energy, thereby catalyzing the methanation of CO2. Preferably, the incident light intensity used in the photothermal catalysis can be 2-3 W / cm 2 .
10. A method for photothermal catalytic CO2 methanation, characterized in that: The method comprises: the nickel-zirconium composite material described in any one of claims 1 to 3 absorbs light energy of at least one of visible light, infrared light and ultraviolet light (preferably, a full-spectrum light source is selected as a driving light source), converts the absorbed light energy into heat energy, and then catalyzes CO2 methanation.